Assessing the Economic Feasibility of Tourism around IKN: Does it Beyond the SDG Standards? - Fitriadi, Fiitriadi; Priyagus, Priyagus; Darma, Dio Caisar (Indonesian Journal of Tourism and Leisure, 2023)
The aim of this paper outlines four urgent reason for tourism to follow up on national targets. In the SDGs document, one of the benchmarks for economic intensity is actualized in the function of tourism in boosting welfare. Using a descriptive approach, secondary data is sourced from government publications, as illustrated by pillar 8 “Decent Work and Economic Growth”. Then, the investigation was converted to IKN (PPU) and 2 zones around IKN (Balikpapan-Kutai Kartanegara) with a frequency of 6 years. With the panel evaluation, several varied estimates were found. First, in parameter 1 (proportion of tourism contribution to GRDP), parameter 2 (number of foreign tourists), and parameter 3 (volume of domestic tourist visits), all the regions analyzed do not meet the SDG target. Second, in parameter 4 (foreign exchange or similar income from tourism), Kukar and Balikpapan have reached the standard, but PPU does not meet the criteria designed by the government. The expectations of this manuscript inspire stakeholders to resolve inequalities in the tourism sector, particularly in inter-line collaboration. Advanced academic studies can adopt or consider existing research through fresher thinking. The broader implications emphasize the maximum tourism potential in IKN.